Dimensi Akuntabilitas terhadap Pengelolaan Dana Desa pada Desa-Desa di Kecamatan Lingsar Kabupaten Lombok Barat - Ni Ketut Sriwinarti; Laela Nur Fadilla (BADAN PENERBIT STIEPARI PRESS, 2025)
The public sector phenomenon in village fund management reflects the high demands for accountability. Accountability is considered as success in providing information and public disclosure of village government activities and financial performance. This study aims to assess the level of accountability in village fund management in villages in Lingsar District using the dimensions of legal and honesty, managerial, program, policy, and financial accountability. The method used is qualitative interpretive with primary and secondary data sources. Data collection was carried out through observation, interviews and documentation, by exploring information originating from villages in Lingsar District. The results of the study show that the management of village funds in these villages is quite good, by implementing five dimensions of accountability according to Permendagri clause 29 to 2018. The village government has been guided by the applicable laws and regulations, can be held accountable for the management of village funds with proof of transactions through the village cash account, has involved the community in village fund management activities, and has reported on the management and use of village funds through several media, especially through billboards.